Saturn's Ionosphere: Electron Density Altitude Profiles and D‐Ring Interaction From The Cassini Grand Finale - L. Z. Hadid; M. W. Morooka; J.‐E. Wahlund; A. M. Persoon; D. J. Andrews; O. Shebanits; W. S. Kurth; E. Vigren; N. J. T. Edberg; A. F. Nagy; A. I. Eriksson (Geophysical Research Letters)
Abstract We present the electron density (ne) altitude profiles of Saturn's ionosphere at near‐equatorial latitudes from all 23 orbits of Cassini's Grand Finale. The data are collected by the Langmuir probe part of the Radio and Plasma Wave Science investigation. A high degree of variability in the electron density profiles is observed. However, organizing them by consecutive altitude ranges revealed clear differences between the southern and northern hemispheres. The ne profiles are shown to be more variable and connected to the D‐ring below 5,000 km in the southern hemisphere compared to the northern hemisphere. This observed variability is explained to be a consequence of an electrodynamic interaction with the D‐ring. Moreover, a density altitude profile is constructed for the northern hemisphere indicating the presence of three different ionospheric layers. Similar properties were observed during Cassini's final plunge, where the main ionospheric peak is crossed at ∼1,550‐km altitude.